Effect of Fake News on the Spread of Covid-19 Pandemic in Nigeria - Okuneye Ademolu Patrick; Uchendu Chinelo Ebele; Lawal Umar Maradun; Muhammad Ridwan; Omotola Ogunbola (Britain International for Academic Research (BIAR) Publisher, 2025)
The spread of fake news during the COVID-19 pandemic in Nigeria, as in many other countries, had significant effects, exacerbating the challenges faced by public health authorities, governments, and citizens. In Nigerian context, social media is a means of keeping up with occurrences all over the globe and is used to shed light as regards the Nigerian situation, the ability to sieve authentic information from an avalanche of half-truths and false information available on social media networks is a challenge in Nigeria. In Nigeria, tackling this issue effectively during the pandemic was critical to improving public health outcomes and societal trust. The paper argues that social media has become an essential part of human life as it allows remote creation of contents for the purpose of entertainment and dissemination of information, making information sharing easier and faster in Nigeria and the world at large. The paper concludes that addressing fake news requires a combination of education, regulation, and collaboration between governments, civil society, and media organizations. Thus, the outbreak of Covid-19 in Nigeria spurred a digitalized reaction with citizen surfing about Covid-19 content to gather information about the virus. Facebook, Instagram, WhatsApp and Twitter, appeared to be among the prominent platforms consulted by Nigerians to create awareness on Covid-19 in the country.